2019
DOI: 10.1016/j.jgr.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

High frequency somatic embryogenesis and plant regeneration of interspecific ginseng hybrid between Panax ginseng and Panax quinquefolius

Abstract: BackgroundInterspecific ginseng hybrid, Panax ginseng × Panax quenquifolius (Pgq) has vigorous growth and produces larger roots than its parents. However, F1 progenies are complete male sterile. Plant tissue culture technology can circumvent the issue and propagate the hybrid.MethodsMurashige and Skoog (MS) medium with different concentrations (0, 2, 4, and 6 mg/L) of 2,4-dichlorophenoxyacetic acid (2,4-D) was used for callus induction and somatic embryogenesis (SE). The embryos, after culturing on GA3 supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 57 publications
1
12
0
2
Order By: Relevance
“…For example, somatic embryos are used as transformation materials for alfalfa, American chestnut, cassava, cotton, grapevine, maize, mango, melon, Norway spruce, papaya, rose, tea tree, and walnut (Umbeck et al, 1987; Mcgranahan et al, 1988; Robertson et al, 1992; Fitch et al, 1993; Li et al, 1996; Brettschneider et al, 1997; Trinh et al, 1998; Mondal et al, 2001; Akasaka-Kennedy et al, 2004; Chavarri et al, 2004; Li et al, 2006; Polin et al, 2006; Vergne et al, 2010). In addition, the regeneration capacity of somatic embryos has made somatic embryogenesis a common method through which to clonally propagate economically important trees or herbal plants (Joshee et al, 2007; Nordine et al, 2014; Guan et al, 2016; Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, somatic embryos are used as transformation materials for alfalfa, American chestnut, cassava, cotton, grapevine, maize, mango, melon, Norway spruce, papaya, rose, tea tree, and walnut (Umbeck et al, 1987; Mcgranahan et al, 1988; Robertson et al, 1992; Fitch et al, 1993; Li et al, 1996; Brettschneider et al, 1997; Trinh et al, 1998; Mondal et al, 2001; Akasaka-Kennedy et al, 2004; Chavarri et al, 2004; Li et al, 2006; Polin et al, 2006; Vergne et al, 2010). In addition, the regeneration capacity of somatic embryos has made somatic embryogenesis a common method through which to clonally propagate economically important trees or herbal plants (Joshee et al, 2007; Nordine et al, 2014; Guan et al, 2016; Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[66,67] Somatic embryo-genesis is an important and reliable regeneration method for establishing true-type clones of many plant species. [68,69] Kim et al [70] conducted a tissue culture study on hybrid Asian/American ginseng (Pgq) and found the optimal condition to induce callus and embryogenesis was MS medium containing 2 mg/L 2,4-D. The Pgq explants produced somatic embryos on MS medium after eight weeks of culture, and somatic embryos germinated rapidly on Schenk and Hilderbrandt (SH) medium containing 5 mg/L GA within two weeks.…”
Section: Induction Of Somatic Embryos From American Ginsengmentioning
confidence: 99%
“…Kim et al [70] . conducted a tissue culture study on hybrid Asian/American ginseng (Pgq) and found the optimal condition to induce callus and embryogenesis was MS medium containing 2 mg/L 2,4‐D.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [56] studied the tissue culture of F1 plant propagation in a ginseng hybrid (P. ginseng × P. quinquefolius) to solve the seedless problem. In addition, some research groups have attempted mutation breeding using irradiation or chemicals, but they did not develop new ginseng varieties; they did confirm plants with high ginsenosides [59][60][61][62][63].…”
Section: Increasing the Genetic Diversity Of The Nac's Ginseng Germplasmmentioning
confidence: 99%